A Prospective Analysis of the Effects of a Powder-Type Hemostatic Agent on the Short-Term Outcomes after Liver Resection - MeeYoung Kang; Jai Young Cho; Ho-Seong Han; Yoo-Seok Yoon; Hae Won Lee; Boram Lee; Yeshong Park; Jinju Kim (Medicina, 2024)
Background and Objectives: Postoperative bleeding is a significant cause of morbidity and mortality following liver resection. Therefore, it is crucial to minimize bleeding during liver resection and effectively manage it when it occurs. Arista® AH (Becton, Dickinson and Company, Franklin Lakes, NJ, USA) is a microporous polysaccharide hemosphere (MPH), a new plant-derived polysaccharide powder hemostat that can be applied to the entire surgical field. This study prospectively assessed the effectiveness of Arista for bleeding control when applied intraoperatively to the liver resection surface. Materials and Methods: Data were collected at Seoul National University Bundang Hospital for patients who underwent liver resection owing to malignant hepatocellular carcinoma or benign liver diseases. We compared the outcomes between 45 patients managed with Arista® AH (data were prospectively collected between September 2022 and May 2023) and 156 patients managed without the use of Arista® AH (data were retrospectively collected between January 2021 and December 2021). Results: There were no significant differences in patient characteristics between the two groups. The estimated blood loss (EBL) was significantly lower in the Arista® AH group compared with the control group (495.56 ± 672.7 mL vs. 691.9 ± 777.5 mL, p = 0.049). The mean postoperative hospital stay was significantly shorter in the Arista® AH group (5.93 ± 1.88 days vs. 6.94 ± 4.17 days, p = 0.024). The time to Jackson-Pratt drain removal was also significantly shorter in the Arista® AH group (4.64 ± 1.31 days vs. 5.30 ± 2.87 days, p = 0.030). The patient subgroup was divided into four categories based on the type of resection and the presence or absence of cirrhosis. Within the subgroup of major resections in non-cirrhotic patients, the Arista® AH group demonstrated significantly better outcomes compared to the control group, showed lower EBL, reduced need for blood transfusions, decreased volume of drain fluid collected within 48 h, earlier removal of drains, and shorter hospital stays. In contrast, for the other subgroups such as minor resection (both non-cirrhotic and cirrhotic) and major resection with cirrhosis, the differences between the Arista® AH and control groups in various parameters like EBL, blood transfusion rates, drain fluid volume, time to drain removal, and duration of hospital stay were not statistically significant. Conclusions: Arista® AH significantly improved intraoperative blood management and postoperative recovery in patients undergoing liver resection, particularly in non-cirrhotic patients who underwent major resection.